MODERNIZATION OF MODEL FOR INITIATION OF INVESTMENT PROJECTS AS A FACTOR OF BALANCED MAINTENANCE OF REGION’S INVESTMENT-INNOVATIONAL ACTIVITY - Anatolievich Doroshenko, Yuri; Miroslavovna Bukhonova, Sophia; Vladimirovna Somina, Irina; Victorovich Manin, Andrei (Journal of Applied Engineering Science, 2014)
In recent decades, because of globalization, development of social, information technologies and some other reasons cities and regions of the world have received the brand new possibilities of economic and cultural development. Barcelona and Sydney, Vancouver and Helsinki, separate parts of Zurich and Strasburg, alone with spread row of provincial and little-known towns and regions, took advantages of new opportunities and obtained a high-capacity inflow of investments and tourists, increase of business and local communities’ activity, new political weigh and cultural significance. As a result, at these territories, the quality of life increased, as much as integration degree of political, business, and cultural structures into national and international area, including investment. In Russia new possibilities were being explored by each territory according to its opportunities, within the programs of Russia’s regions innovational development. Nowadays, because of accumulated international and domestic experience, we can easily say, that the time has come to expand the limits by embracement of technological innovational activity by investment and social-cultural approaches to development and branding of territories.
Keywords: Development models; Development technologies; Region; Investment-innovational activity; Investment potential; Innovation development